THE GENDERED KNOWLEDGE OF HIV/AIDS AMONG URBAN UNIVERSITY STUDENTS IN SOUTHERN ETHIOPIA - Marianne Paul; Basanti Majumdar; Noori Akhtar-Danesh; Sheryl Boblin; Diana Sherifali (European Scientific Journal, ESJ, 2013)
The HIV/AIDS epidemic continues to claim millions of lives worldwide. Africa alone represents the majority of HIV/AIDS cases, where the young aged 16-30, are at greatest risk. The research suggests a gender dichotomy in HIV/AIDS knowledge levels between male and female students in Ethiopia. The purpose of this research is to explore the gendered knowledge of HIV/AIDS among a group of Ethiopian male and female post-secondary students. An observational study was conducted among 126 female and 101 male college and university students. The HIV Knowledge Questionnaire was used to measure participants’ knowledge. The statistical t-test demonstrated no difference between male and female HIV knowledge scores (t=0.6, df =225, p=0.4). The study findings demonstrate the call to address the knowledge gap in HIV sexual transmission among a vulnerable population. Future research is needed such that HIV/AIDS awareness campaigns can be specifically tailored to the student population within the Ethiopian context.